1998
DOI: 10.1212/wnl.51.5.1282
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind trial of gabapentin monotherapy for newly diagnosed partial seizures

Abstract: Gabapentin at 900 or 1,800 mg/day is effective and safe as monotherapy for patients with newly diagnosed partial epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(106 citation statements)
references
References 11 publications
4
96
0
6
Order By: Relevance
“…Gabapentin was initially introduced as an anti-epileptic drug for the treatment of partial seizures with or without secondary generalization [7,9,10,11,12]. Besides epilepsy, it is used for the treatment of migraine, bipolar illness or movement disorders, namely restless legs syndrome, essential tremor or nystagmus [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin was initially introduced as an anti-epileptic drug for the treatment of partial seizures with or without secondary generalization [7,9,10,11,12]. Besides epilepsy, it is used for the treatment of migraine, bipolar illness or movement disorders, namely restless legs syndrome, essential tremor or nystagmus [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin (GBP) is a clinically useful antiepileptic drug (AED) as adjunctive and nionotherapy (1)(2)(3)(4). It is useful in the management of neuropathic pain (5).…”
mentioning
confidence: 99%
“…These studies concluded that the newer agents were found to be better tolerated than the old AEDs. Chadwick et al (41) reported that the discontinuation rate due to adverse effects in adolescents and adults newly diagnosed with partial or generalized epilepsy was found to be lower in the higher dosed gabapentin treated patients (13.5%) than among carbamazepine treated patients (24%) with dizziness, fatigue and somnolence more frequent in the carbamazepine treated group. Gabapentin doses >1,800 mg/day were as well tolerated as doses less than or equal to 1,800 mg/day and were associated only with asthenia, headache and dizziness in patients of age 12 years and older with a mean age of 37 years (42).…”
Section: Safety and Tolerability Of New Versus Old Aedsmentioning
confidence: 99%